Alexander and the wind-up mouse. - Lionni, Leo, 1910- (New York : Knopf/Pantheon, 1974)
Alexander, a real mouse, wants to be a toy mouse like his friend Willy until he discovers Willy is to be thrown away.
Wilson's Children.
Elem. School Library Collection.
Caldecott Medal/Honor.
4.7
K-3
Caldecott Medal/Honor, 1995.
Keywords: Mice -- Fiction; Mice -- Fiction; Mice -- Fiction; Caldecott honor book